Language Proficiency and Hiring of Immigrants: Evidence from a New Field Experimental Approach - Magnus Carlsson; Stefan Eriksson; Dan-Olof Rooth (Institute of Labor Economics (IZA), 2023)
Labor markets in advanced economies have undergone substantial change in recent decades due to globalization, technological improvements, and organizational changes. Due to these developments, oral and written language skills have become increasingly important even in less skilled jobs. Immigrants – who often have limited skills in the host country language upon arrival – are likely to be particularly affected by the increase in language requirements. Despite this increase in literacy requirements, little is known about how immigrants' language proficiency is rewarded in the labor market. However, estimating the causal effect of immigrants' language skills on hiring is challenging due to potential biases caused by omitted variables, reverse causality, and measurement error. To address identification problems, we conduct a large-scale field experiment, where we send thousands of fictitious resumes to employers with a job opening. With the help of a professional linguist, we manipulate the cover letters by introducing common second-language features, which makes the resumes reflect variation in the language skills of real-world migrants. Our findings show that better language proficiency in the cover letter has a strong positive effect on the callback rate for a job interview: moving from the lowest level of language proficiency to a level similar to natives almost doubles the callback rate. Consistent with the recent development that language proficiency is also important for many low- and medium-skilled jobs, the effect of better language skills does not vary across the vastly different types of occupations we study. Finally, the results from employer surveys suggest that it is improved language skills per se that is the dominant explanation behind the language proficiency effect, rather than language skills acting as a proxy for other unobserved abilities or characteristics.
Keywords: F22; J15; J24; 330; labor migrants; language proficiency; language skills; human capital; field experiment